Understanding Australian Aboriginal tertiary student needs - Oliver, Rhonda; Rochecouste, J.; Bennell, D.; Anderson, R.; Cooper, I.; Forrest, S.; Exell, M. (Sciedu Press, 2013)
Drawing from a study of the experiences of Australian Aboriginal and Torres Strait Islander university students, this paper presents an overview of the specific needs of these students as they enter and progress through their tertiary education. Extracts from a set of case studies developed from both staff and student interviews and an online survey are used to illustrate what we have categorised as the emotional, motivational, financial, study, literacy and transitional needs of the particular cohort of students. Our findings, supported strongly by other current research, point to the need for a whole-of-university approach to enhancing the educational and subsequent employment opportunities for Aboriginal students. This includes acknowledging cultural and familial responsibilities, recognising and accommodating Aboriginal knowledge, and ensuring equitable experiences of university life.